2021
DOI: 10.3390/ijms22157869
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Approaches through Modulating the Autophagy Process for Skin Barrier Dysfunction

Abstract: Autophagy is an attractive process to researchers who are seeking novel potential treatments for various diseases. Autophagy plays a critical role in degrading damaged cellular organelles, supporting normal cell development, and maintaining cellular homeostasis. Because of the various effects of autophagy, recent human genome research has focused on evaluating the relationship between autophagy and a wide variety of diseases, such as autoimmune diseases, cancers, and inflammatory diseases. The skin is the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 126 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Autophagy plays a substantial role in the homeostasis of skin development. Loss or impairment of autophagy has been associated with a number of skin conditions (50). For instance, the downregulation of LC3 (51) and the upregulation of p62 (52), which reflect a blockage of autophagy, are involved in inflammation in psoriasis; likewise, the autophagy activator rapamycin alleviates imiquimod-induced psoriasis-like dermatitis (51).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a substantial role in the homeostasis of skin development. Loss or impairment of autophagy has been associated with a number of skin conditions (50). For instance, the downregulation of LC3 (51) and the upregulation of p62 (52), which reflect a blockage of autophagy, are involved in inflammation in psoriasis; likewise, the autophagy activator rapamycin alleviates imiquimod-induced psoriasis-like dermatitis (51).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is essential for skin homeostasis. The dysfunctional regulation of autophagy responses leads to several skin disorders, including psoriasis [ 13 , 14 ]. LC3 and p62 are two well-characterized autophagy biomarkers used to represent and quantify the status of autophagy [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunctional regulation of autophagy responses leads to several skin disorders, including psoriasis [ 13 , 14 ]. LC3 and p62 are two well-characterized autophagy biomarkers used to represent and quantify the status of autophagy [ 13 , 14 , 15 ]. Previous studies reported that LC3B protein expression was lower in psoriatic lesional skin than in non-lesional skin [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, autophagy may also regulate key inflammatory cytokines in tumors. Accordingly, autophagy leads to opposing consequences for the tumor since it works as both a tumor suppressor and a tumor promotor [ 13 ]. Figure 2 represents autophagy signaling pathways involved in cancer-associated inflammation.…”
Section: Introductionmentioning
confidence: 99%